An algorithm for finding candidate synaptic sites in computer generated networks of neurons with realistic morphologies - Van Pelt, Jaap; Carnell, Andrew; De Ridder, Sander; Mansvelder, Huibert D.; Van Ooyen, Arjen (Frontiers in Computational Neuroscience, 2010)
Neurons make synaptic connections at locations where axons and dendrites are sufficient close in space. Typically the required proximity is based on the dimensions of dendritic spines and axonal boutons. Based on this principle one can search those locations in networks formed by reconstructed neurons or computer generated neurons. Candidate synapses are then located where axons and dendrites are within a given criterion distance from each other. Both experimentally reconstructed and model generated neurons are usually represented morphologically by piece wise linear structures (line pieces or cylinders). Proximity tests are then to be performed on all pairs of line pieces from both axonal and dendritic branches. Applying just a test on the distance between line pieces may result in local clusters of synaptic sites when more than one pair of nearby line pieces from axonal and dendritic branches is sufficient close, and may introduce a dependency on the length scale of the individual line pieces. The present paper describes a new algorithm for defining locations of candidate synapses which is based on the crossing requirement of a line piece pair, while the length of the orthogonal distance between the line pieces is subjected to the distance criterion for testing 3D proximity